Granulomatous lung inflammation is nanoparticle type-dependent. (2nd January 2018) - Pacheco, Yves; Ponchon, Marine; Lebecque, Serge; Calender, Alain; Bernaudin, Jean François; Valeyre, Dominique; Iglarz, Marc; Strasser, Daniel S.; Studer, Rolf; Freti, Diego; Renno, Toufiq; Bentaher, Abederrazzaq
ABSTRACT: Background: Nanoparticles are increasingly suspected as a strong etiologic factor of granuloma formation.Aim of the Study: The aim of our study was to compare lung inflammatory response and histology changes following exposure of mice to two widely used nanoparticles: carbon nanotubes (MWCNT) and cadmium-based nanoparticles (QDOT705) in an attempt to better our understanding of granulomatous inflammation.Materials and Methods: Various groups of mice were included: control mice and mice that were intranasally instilled with QDOT or MWCNT. At defined time points post-challenge, bronchoalveolar lavages (BALs) and lung tissues were collected to study inflammatory and histologic changes.Results: Analyses of lung BAL fluids and tissues of nanoparticles-challenged mice in comparison to controls found: (1) increased cellularity in BALs, (2) increase of total protein concentration, LDH activity and proteolytic activity in BALs; (3) patchy granulomas, (4) macrophages, CD3 ± T, Treg and B cell infiltration in granulomatous areas; and (5) altered regulation of key inflammatory mediators and receptors. Importantly, these changes were nanoparticle type-dependent.Conclusion: Our work enhances understanding of nanoparticles-induced lung inflammatory and histological changes that result in granuloma formation. We provide compelling evidence that not only exposure to nanoparticles leads to granulomatous lung inflammation, but the severity of this latter is nanostructure type-dependent. Of importance, while nanotechnology has the potential to revolutionize various fields including medicine, nanoparticles form the potential for an entirely new lung health risk that it is necessary to take seriously into consideration by setting up and/or reinforcing adequate safety measures.